Monolingual foreign language dictionary: Guided Visits as instrumentalization for autonomy in language learning - Hwang, Alvaro David [UNESP] (Federal Univ Ceara, 2021)
The present work is inspired by the concern of many lexicography scholars in promoting the role of dictionaries in language teaching / learning. Based on theoretical support from authors such as Binon and Verlinde (1999), Lehmann (2014) and Galisson (1983, 1987), whose works address the role of the dictionary as a learning tool, we propose here a guided visit to a monolingual French-language dictionary, such as those that are commonly proposed for a pedagogical approach in museums, cathedrals, and monuments, in order to promote, with potential users of lexicographic works of this nature, a familiarization with lexicographic communication and, therefore, interest in a more attentive reading of the information, having as main objective the understanding that the look-up can become a space of discoveries that goes beyond what may have motivated it. This journey has a purely demonstrative value, so that, given its multiple possible configurations and the learner's interest in specific and varied aspects of the description, it can be enriched and redirected in other ways by those who understand that leaving the user to his fate, armed only with the domain of alphabetical order, is not enough to ensure a good use of dictionaries. In this sense, the guided visits would also have an important role as a seduction exercise, in order to strengthen the user's relationship with the dictionary.
Keywords: Lexicography; Monolingual dictionary; Guided visits